Influência do sedimento no processo de remoção de nitrogênio por nitrificação/desnitrificação em lagoas de polimento - Valéria Antônia Justino Rodrigues (2016)
Polishing ponds are used as post-treatment units for effluents from UASB reactors. This technique is very efficient in removing organic matter, pathogens and, depending on operating conditions, can remove nitrogen. However, there is much controversy in the literature regarding removal mechanisms (volatilization, assimilation, sedimentation and nitrification/denitrification) that occur in ponds. Some researchers have reported on the importance of the sludge layers (aerobic, anoxic and anaerobic layers), while others reported about algal assimilation. The aim of this study was to evaluate the sludge role in the nitrogen removal process in polishing ponds. For this, experiments were carried out to evaluate the influence of sludge, to determine the experimental and theoretical (based on the Monod model) nitrogen removal rates, the quantification of the genes of nitrogen cycle bacteria and evaluation of mixing conditions and stratification in two ponds treating UASB reactor effluent. One of the ponds had accumulated sludge throughout its 10 years of operation, while the other had the sludge removed just before the experiments. It was observed that the pond with sludge, even with 40% of the volume filled (lower HRT), presented a performance similar to the pond without sludge for the variables COD, BOD, TSS and VSS and were significantly different in relation to nitrogenous compounds (ammonium, nitrate and nitrite). Both lagoons had high nitrate removal potential (3.23 and 3.03 g/m2.d) after the application of 30 g N-NO3-/m3. However, CD values did not lead to a good adjustment in relation to temperature, oxygen, alkalinity, organic matter and ammonium or nitrate due to the sensitivity of this term to the mean values found by the model used (CDnitrification = -0.497 and CDdenitrification = -0.207). The abundance of bacteria decreased from the top to the bottom of the pond with sludge and showed no major differences in layers of the ponds without sludge. The ponds presented different mixing cycles, with the occurrence of anaerobic environments in some hours of the dawn until the early morning. The daily mixing cycles supply DO and nutrients that are carried to the bottom and stratification of the lagoons from dawn to early morning (anaerobic conditions throughout the ponds) allowed the activity of different groups of bacteria in the nitrogen cycle. With the study, it was observed that nitrogen removal in the investigated ponds occurred intensely due to the high photosynthetic activity of algae in the liquid column until where the solar radiation can reach (30 cm) and by nitrification and simultaneous denitrification in the sediment, besides the participation of other mechanisms of the nitrogen cycle in the removal process.